Effectiveness of Structured Teaching Program Regarding Placental Examination among Staff Nurses at Baghdad Teaching Hospitals - Sarab Nasr; Rabea Mohsen Ali (Kufa Journal for Nursing Sciences)
Objectives: The study aims to evaluate the nurse-midwives’ knowledge and practices regarding placenta examination in a delivery room in Baghdad teaching hospitals.